Ukraine Girls and Liverpool Boys Back in the USSR: Revisiting The Beatles in Times of Trouble and War - Alarcão, Miguel (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2022)
This paper was prompted by two totally unconnected but highly evocative events: The Beatles International Conference, organized by the Lisbon branch of CETAPS at NOVA (June 2021), and the Russian military invasion of Ukraine (February 2022). My purpose in drawing them together is to offer some brief comments on “Back in the USSR”, the opening track of the double LP The Beatles (November 1968), the first edited by Apple Records, and usually known as “The White Album”.